2019
DOI: 10.1186/s12883-019-1499-8
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of oral diet based on flexible endoscopic evaluation of swallowing (FEES) in acute stroke patients: a cross-sectional hospital-based registry study

Abstract: BackgroundDiagnosing dysphagia in acute stroke patients is crucial, as this comorbidity determines morbidity and mortality; we therefore investigated the impact of flexible nasolaryngeal endoscopy (FEES) in acute stroke patients.MethodsThe FEES investigation as performed in acute stroke patients treated at a large university hospital, allocated as a standard procedure for all patients suspected of dysphagia. We correlated our findings with baseline data, disability status, pneumonia, duration of hospitalisatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
(31 reference statements)
1
25
0
1
Order By: Relevance
“…Based on the FEES results, a significant change in diet occurred in 65% of the patient cohort in this study, with diet restrictions being decreased in 60% and increased in 5% of patients. These results are supported by a recent German hospital study by Braun et al [ 28 ]. In 72% of their study cohort, the FEES investigation found relevant dysphagia, which led to an adjustment of diet.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Based on the FEES results, a significant change in diet occurred in 65% of the patient cohort in this study, with diet restrictions being decreased in 60% and increased in 5% of patients. These results are supported by a recent German hospital study by Braun et al [ 28 ]. In 72% of their study cohort, the FEES investigation found relevant dysphagia, which led to an adjustment of diet.…”
Section: Discussionsupporting
confidence: 86%
“…According to Cohen et al, pneumonia prevention does not only include the early detection of swallowing disorders [ 28 ]. Both therapeutic and dietary interventions to reduce aspiration volume and frequency, as well as procedures to reduce the pathogenicity of aspiration, improve larynx sensitivity and respiratory protection mechanisms, as well as cough, and promote cortical plasticity to restore the swallowing function [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study significant lower rates of mortality and aspiration pneumonia were recorded after the change of oral diet based on FEES findings. In only 31% of investigated dysphagic cases on a stroke unit (SU) did the clinical assessment identify a proper oral diet [15]. In this study the change of oral diet based on FEES findings correlated with a better overall outcome at discharge from SU, shorter length of stay, lower rate of aspiration pneumonia, and lower need for mechanical ventilation.…”
Section: Discussionmentioning
confidence: 72%
“…Zbog praktičnih razloga sve se više upotrebljava fiberendoskopska evalu- acija gutanja [4][5][6] . Kao prednosti fiberendoskopske evaluacije gutanja ističu se mogućnost obavljanja pretrage uz postelju bolesnika, izbjegavanje zračenja te mogućnost jednostavnog ponavljanja pretrage u više navrata, a komplikacije kao što su epistaksa i vazovagalna sinkopa su rijetke 60,61 . Fiberendoskopijom je moguće prikazati područje ždrijela i grkljana u trenutku neposredno prije i neposredno nakon gutanja.…”
Section: Dijagnostikaunclassified